The Signal Peptide of the IgE Receptor α-Chain Prevents Surface Expression of an Immunoreceptor Tyrosine-based Activation Motif-free Receptor Pool - Platzer, Barbara (American Society for Biochemistry and Molecular Biology, 2010)
The high affinity receptor for IgE, Fc epsilon receptor I (FcϵRI), is an activating immune receptor and key regulator of allergy. Antigen-mediated cross-linking of IgE-loaded FcϵRI α-chains induces cell activation via immunoreceptor tyrosine-based activation motifs in associated signaling subunits, such as FcϵRI γ-chains. Here we show that the human FcϵRI α-chain can efficiently reach the cell surface by itself as an IgE-binding receptor in the absence of associated signaling subunits when the endogenous signal peptide is swapped for that of murine major histocompatibility complex class-I H2-K(b). This single-chain isoform of FcϵRI exited the endoplasmic reticulum (ER), trafficked to the Golgi and, subsequently, trafficked to the cell surface. Mutational analysis showed that the signal peptide regulates surface expression in concert with other described ER retention signals of FcϵRI-α. Once the FcϵRI α-chain reached the cell surface by itself, it formed a ligand-binding receptor that stabilized upon IgE contact. Independently of the FcϵRI γ-chain, this single-chain FcϵRI was internalized after receptor cross-linking and trafficked into a LAMP-1-positive lysosomal compartment like multimeric FcϵRI. These data suggest that the single-chain isoform is capable of shuttling IgE-antigen complexes into antigen loading compartments, which plays an important physiologic role in the initiation of immune responses toward allergens. We propose that, in addition to cytosolic and transmembrane ER retention signals, the FcϵRI α-chain signal peptide contains a negative regulatory signal that prevents expression of an immunoreceptor tyrosine-based activation motif-free IgE receptor pool, which would fail to induce cell activation.